Comparing solution methods for DSGE models with labor market search - Hong Lan (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
I compare the performance of solution methods in solving a standard real business cycle model with labor market search frictions. Under the conventional calibration, the model is solved by the projection method using the Chebyshev polynomials as its basis, and the perturbation methods up to third order in both levels and logs. Evaluated by two accuracy tests, the projection approximation achieves the highest degree of accuracy, closely followed by the third order perturbation in levels. Although different in accuracy, all the approximated solutions produce simulated moments similar in value.
Keywords: C63; C68; E32; 330; Computational methods; DSGE; Business cycles; Search and matching; Accuracy test